IMPLEMENTATION OF RESTORATIVE JUSTICE BY THE PROSECUTOR'S OFFICE IN SETTLEMENT OF GENERAL CRIMINAL CASES (STUDY OF THE KEBUMEN DISTRICT PROSECUTOR'S OFFICE) - Fariza, Muhammad; Gunarto, Gunarto (UNISSULA Semarang, 2024)
This study aims to determine, examine, and analyze: (1) the implementation of restorative justice by the prosecutor's office in resolving general criminal cases at the Kebumen District Attorney's Office, (2) the obstacles and solutions in the implementation of restorative justice by the prosecutor's office in resolving general criminal cases at the Kebumen District Attorney's Office, (3) as well as the conception of the implementation of restorative justice by the prosecutor's office in resolving general criminal cases in the future based on the Value of Justice. The approach method used in this study is sociological juridical. The specifications of this study are descriptive analytical.Based on the results of the study, it can be concluded that (1) the implementation of restorative justice by the prosecutor's office in resolving general criminal cases at the Kebumen District Attorney's Office is carried out based on the Prosecutor's Regulation Number 15 of 2020 concerning the Termination of Prosecution Based on Restorative Justice. (2) Obstacles and solutions in the implementation of restorative justice by the prosecutor's office in resolving general criminal cases at the Kebumen District Attorney's Office are in the field of legal factors themselves, law enforcement factors, legal facilities or infrastructure factors, community factors, and also cultural factors, where the cultural factor is not considered an obstacle. To address these obstacles, the Kebumen District Attorney's Office is using a solution by conducting socialization about prosecutorial regulations to the public. (3) The concept of implementing restorative justice by the prosecutor's office in resolving general criminal cases in the future based on the Value of Justice, with existing rules and policies, can be formulated into a legal regulation to provide legal certainty, legal strength, and a clear legal basis for law enforcement officers in applying restorative justice. (restorative justice).